Decision to Purchase Local Fruits Based on Halal Traceability: An Evidence in Indonesia - Resista Vikaliana; Raja Zuraidah Raja Mohd Rasi; I Nyoman Pujawan; Irwansyah Irwansyah (Universitas Muslim Indonesia, 2021)
This study aimed to determine the decision to purchase local Indonesian fruit based on the understanding of the halal traceability of local fruit. This study used a quantitative approach, with a sample of 255 consumers who purchased local fruit in the last 3 months. Regression analysis is used to analyze the data from the questionnaire in this study. The results showed that halal traceability positively and significantly affected local fruit purchasing decisions, as indicated by the equation Y = 14.885 + 0.251X. The results of hypothesis testing also prove that there is an influence between halal traceability and local fruit purchasing decisions. While the correlation coefficient is 0.384, meaning that the effect is weak, and the coefficient of determination is 14.8%. The correlation coefficient and the coefficient of determination indicate that other variables not examined in this study influence the local fruit purchasing decisions, which are recommended for further investigation.